'The common ties of our Religion...and strict Commerce’: John Dryden’s Amboyna (1673) and its religious preservation of the Old World - Gavala, Dikaia (Mos Historicus: A Critical Review of European History, 2025)
After the Restoration, the political atmosphere found outlet in the newly reopened theatres as the rise in explicitly titled political plays shows that the public may had developed an appetite for the affairs of state(s) on stage. By closely reading John Dryden’s tragedy Amboyna (1673), a tragedy based on a historical event in colonised Indonesia which continued to haunt the British cultural memory in posterity, this paper seeks to analyse the ways in which religion was instrumental to political support and trade dominance and the role religious differences played in constructing representations of otherness and imperial myths of masterfulness. As Dryden prompted his audience to political action in the play’s concurrent Third Anglo-Dutch War, dramaturgy spoke to the audiences, not least because of the achronic appeal of politics in the symbolic realm.